Attosecond synchronization of extreme ultraviolet high harmonics from crystals. (17th June 2020) - Vampa, Giulio; Lu, Jian; You, Yong Sing; Baykusheva, Denitsa R; Wu, Mengxi; Liu, Hanzhe; Schafer, Kenneth J; Gaarde, Mette B; Reis, David A; Ghimire, Shambhu
Abstract: The interaction of strong near-infrared (NIR) laser pulses with wide-bandgap dielectrics produces high harmonics in the extreme ultraviolet (XUV) wavelength range. These observations have opened up the possibility of attosecond metrology in solids, which would benefit from a precise measurement of the emission times of individual harmonics with respect to the NIR laser field. Here we show that, when high-harmonics are detected from the input surface of a magnesium oxide crystal, a bichromatic probing of the XUV emission shows a clear synchronization largely consistent with a semiclassical model of electron–hole recollisions in bulk solids. On the other hand, the bichromatic spectrogram of harmonics originating from the exit surface of the 200 μ m-thick crystal is strongly modified, indicating the influence of laser field distortions during propagation. Our tracking of sub-cycle electron and hole re-collisions at XUV energies is relevant to the development of solid-state sources of attosecond pulses.